2020
DOI: 10.1002/csc2.20023
|View full text |Cite
|
Sign up to set email alerts
|

Partial substitution of mineral fertilizer with biofertilizer enhances cauliflower nutritional quality, yield, and soil characteristics

Abstract: Cauliflower (Brassica oleracea L. var. botrytis L.) is as an important ingredient in many healthy diets worldwide, but there is a lack of scientific knowledge about fertilizer management during cauliflower production. We conducted field experiments in Yuzhong, China, in 2015 and 2016 to determine the effects of the integrated use of biofertilizer and a reduced rate of mineral fertilizers on cauliflower growth, quality, and yield and on soil characteristics. Three different rates of mineral fertilizer (60, 80,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…In this study, we found that in lettuce, the levels of soluble sugars, soluble protein, and vitamin C increased to varying degrees in the T1–4 treatment groups ( Figure 4 ). Similar results have also been reported in tomatoes ( Brunetti et al, 2019 ) and cauliflowers ( Yang et al, 2020a ). Based on these findings, we speculate that the application of reduced chemical fertilizer combined with bio-organic fertilizer can promote the yield and quality of lettuce by improving soil chemical properties and microbial communities ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that in lettuce, the levels of soluble sugars, soluble protein, and vitamin C increased to varying degrees in the T1–4 treatment groups ( Figure 4 ). Similar results have also been reported in tomatoes ( Brunetti et al, 2019 ) and cauliflowers ( Yang et al, 2020a ). Based on these findings, we speculate that the application of reduced chemical fertilizer combined with bio-organic fertilizer can promote the yield and quality of lettuce by improving soil chemical properties and microbial communities ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 89%
“…The soluble sugar and VC content of 'yellow rose' cabbage increased, while nitrate content decreased when the plants were applied by reduced nitrogen with bio-organic fertilizer (Table 3, Figure 3). Similar results were reported by Wang [39] on cabbages, by Brunetti [40] on tomato and by Yang [41] on cauliflower. The latest research shows that reducing nitrogen by 20-30% with bio-organic fertilizer had the best quality improvement effect on cabbage [42] and tomato [43].…”
Section: Effects Of Reduced Nitrogen With Bio-organic Fertilizer On the Photosynthetic Characteristics And Quality Of 'Yellow Rose' Cabbasupporting
confidence: 90%
“…Research suggests that organic matter as an overall indicator is essential for soil quality, which can bring many benefits to soil and plants [38]. The application of organic fertilizer not only improves soil enzyme activity [39], but also improves the available macronutrient content and increases soil micronutrient availability [40]. In this study, nitrogen reduction with bio-organic fertilizer improved the invertase and FDA soil activities (N2 and S2) (Figure S1), as well as K and Zn contents (N2) compared with conventional fertilization.…”
Section: Effects Of Nitrogen Reduction With Bio-organic Fertilizer On...mentioning
confidence: 99%